2015
DOI: 10.1002/jmor.20391
|View full text |Cite
|
Sign up to set email alerts
|

Convergence vs. Specialization in the ear region of moles (mammalia)

Abstract: We investigated if and how the inner ear region undergoes similar adaptations in small, fossorial, insectivoran-grade mammals, and found a variety of inner ear phenotypes. In our sample, afrotherian moles (Chrysochloridae) and the marsupial Notoryctes differ from most other burrowing mammals in their relatively short radii of semicircular canal curvature; chrysochlorids and fossorial talpids share a relatively long interampullar width. Chrysochlorids are unique in showing a highly coiled cochlea with nearly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 81 publications
(119 reference statements)
2
16
0
Order By: Relevance
“…From Ekdale’s data, only the pangolin Manis and an extinct elephantimorph of uncertain identity have canals of similar proportions. Among subterranean mammals, data tabulated by Crumpton et al [82] show that certain golden moles and the marsupial mole Notoryctes can be added to that list, while the membranous semicircular canals of the spalacid mole-rat Spalax have similar dimensions to those of Fukomys [33]. ‘Short and fat’ canals have evidently evolved several times in parallel among subterranean mammals, although they are not found in all species.…”
Section: Discussionmentioning
confidence: 99%
“…From Ekdale’s data, only the pangolin Manis and an extinct elephantimorph of uncertain identity have canals of similar proportions. Among subterranean mammals, data tabulated by Crumpton et al [82] show that certain golden moles and the marsupial mole Notoryctes can be added to that list, while the membranous semicircular canals of the spalacid mole-rat Spalax have similar dimensions to those of Fukomys [33]. ‘Short and fat’ canals have evidently evolved several times in parallel among subterranean mammals, although they are not found in all species.…”
Section: Discussionmentioning
confidence: 99%
“…The inner ear of R. sinensis possesses some characteristics which are connected with low frequency hearing and subterranean way of life. A long and highly coiled cochlea (3.25 turns) is considered a trait which enhances low frequency sensitivity (Crumpton et al, ). A high number of cochlear coils is typical for species with prevalent subterranean activity (Müller et al, ; Burda et al, ; Burda, ) but also for caviomorphs with different hearing ecologies (Pye, ; Begall and Burda, ; Teudt and Richter, ).…”
Section: Discussionmentioning
confidence: 99%
“…From mapping ossicular size onto available phylogenies, Asher et al () and Crumpton et al () suggested that the small ear ossicles found in golden moles such as Amblysomus might represent a derived morphology among crown‐group chrysochlorids. Huetia was found to be the basal‐most species of the group in one phylogenetic study (Bronner et al, ), so the size of its malleus is particularly significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, Asher et al () noted that the golden mole taxa most frequently reconstructed as basal in their Bayesian analyses had ‘slightly enlarged’ ( Huetia ), elongated ( Chrysochloris , Cryptochloris ) or enlarged and globular ( Eremitalpa ) mallei. Asher et al () raised the possibility that small ossicles may, in fact, be derived among extant golden moles, a suggestion later echoed by Crumpton, Kardjilov, and Asher (), based on similar phylogenetic arguments.…”
Section: Introductionmentioning
confidence: 92%